INCLUSIVE EDUCATION STRATEGIES FOR CHILDREN WITH MOSCOW DISABILITIES AND CONDITIONS FOR THEIR IMPLEMENTATION - Razzoqova Kumush; Nurmatova Gulmira (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article analyzes inclusive education strategies for children with musculoskeletal disorders and the conditions necessary for their implementation. Adapted teaching methods, physical environment, pedagogical approaches and the level of training of teachers are considered as important factors for the full inclusion of children with special needs in the educational process. The article also discusses the existing opportunities in institutions, existing problems and ways to overcome them.